A new large hypercarnivorous crocodyliform from the Maastrichtian of Southern Patagonia, Argentina - Novas, Fernando Emilio (2025)
The first crocodyliform specimen from the Maastrichtian Chorrillo Formation (AustralBasin, Patagonia) is here described. The discovery was made about 30 km to theSW of the town of El Calafate (Province of Santa Cruz, Argentina) and consists of abeautifully preserved and articulated skull and jaws, and part of the postcranial skeletonthat were preserved encased in a large concretion. This new taxon belongs to thenotosuchian clade Peirosauridae, representing the latest and southernmost recordfor this group of crocodyliforms. The new taxon is recovered as closely related toother robust and broad-snouted peirosaurids that lived by the end of the CretaceousPeriod, such as Colhuehuapisuchus from the Maastrichtian of Central Patagonia andMiadanasuchus oblita from the Maastrichtian of Madagascar. The completeness ofthe new specimen reveals, for the first time, the anatomy and body plan of a largeand broad snouted peirosaurid. The new taxon bears large ziphodont teeth,a broad oreinirostral snout that is only slightly longer than 50% the skull length, anda deep adductor chamber in the temporal region and posterior mandibular ramus.The anterior region of its postcranial skeleton is preserved and shows broad scapulaand a robust humerus features previously known in large predatorial notosuchians.The new crocodyliform adds to the predatorial component of terrestrial ecosystems athigh paleolatitudes by the end of the Cretaceous Period.